Effect of perforated concave delta winglet vortex generators on heat transfer and flow resistance through the heated tubes in the channel. Issue 5 (29th July 2022) - Effendi, Yafid; Prayogo, Amrih; Syaiful,; Djaeni, M.; Yohana, Eflita
ABSTRACT: This study focuses on improving heat transfer from the surface of heated tubes to airflow in the channel. Perforated concave delta winglet vortex generators, which have not been used in previous studies, were implemented in this study to increase the heat transfer rate. In this experimental study, the comparison of perforated concave delta winglet and perforated delta winglet was investigated in terms of increased heat transfer from a heated six-tube surface to the flow in a rectangular channel. The experimental results indicated that the use of perforated concave delta winglet vortex generators could increase the heat transfer rate of 46.3% toward the baseline. However, the optimal thermal-hydraulic performance was found in the use of the concave delta winglet at 1.37 with a staggered vortex generators arrangement. The results of this study indicated that the use of perforated vortex generators could reduce the pressure drop with a slight decrease in the heat transfer rate.